Targeting Coping to Improve Surgical Outcomes in Pediatric Patients With Median Arcuate Ligament Syndrome: Feasibility Study - Stiles-Shields, Colleen; Osos, Sylwia; Heilbrun, Anna; Feldman, Estée C. H.; Mak, Grace Zee; Skelly, Christopher L.; Drossos, Tina (Frontiers in Psychology, 2021)
Background: Median Arcuate Ligament Syndrome (MALS) is a vascular compression syndrome leading to postprandial epigastric pain, nausea, and weight loss; it can be treated surgically. While most patients report improved quality of life following surgical intervention, 30% continue to experience chronic abdominal pain. Pre-surgical diagnoses of depression and/or anxiety have been found to significantly predict post-surgical: quality of life, highest experience of pain, anxiety, and parent- and self-reported coping strategies. As such, increasing the coping strategies of pediatric patients with MALS may impact their post-surgical outcomes. The purpose of the current study was to: 1) implement a pre-operative cognitive behavioral therapy protocol with a focus on psychoeducation and coping strategies; and 2) determine feasibility of a pre-surgical intervention for this population. Method: Children (<18 years of age) with a diagnosis of MALS who were eligible for surgical intervention were invited to participate in a seven-week in-person or video-based pre-surgical cognitive behavioral therapy intervention. Psychiatric comorbidities were assessed at baseline and post-surgery; patient-reported distress, pain interference and intensity, health-related quality of life, and health status were assessed at four time points (baseline, week 4, week 7, and post-surgery). Descriptive analyses were used to characterize the sample, assess feasibility outcomes (i.e., attrition rates), and explore symptom-based outcomes across time. Results: Twelve pediatric patients (M age = 15.2±1.7; 91.7% female) and their parents (91.7% mothers) participated. Feasibility metrics based on protocol completion were exceeded for engagement at the stages of consent (68.4% vs. goal of ≥50%), treatment initiation (92.3% vs. 85%), and treatment completion (84.6% vs. 75%). Out of the 12 participants, nine (75%) met criteria for at least one comorbid psychiatric diagnosis at baseline and nine (75%) elected to undergo MALS surgery after completing the intervention. Conclusions: The intervention implementation was feasible, despite chronic pain symptoms experienced by the sample, a high prevalence of psychiatric diagnoses, and an international pandemic, suggesting that it would be beneficial to further evaluate the efficacy of the intervention. Future research should include stakeholder input in the design, deployment, and evaluation of a pilot efficacy trial of pre-surgical cognitive behavioral therapy for pediatric patients with MALS.